2012
DOI: 10.4236/ajcc.2012.14015
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Adaptive Capacity in Unembanked Neighborhoods? An Exploration into Stakeholder Support for Adaptive Measures in Rotterdam, The Netherlands

Abstract: Cities in deltas are vulnerable to climate change, especially their unembanked neighborhoods that are not protected by dikes. Rising sea levels and extreme water levels in the rivers can lead to the flooding of these urban areas. The Netherlands has a long history in water management. However, building dikes and the elevation of land are traditionally treated as rather stand-alone measures. Attention is rarely paid to the surrounding area, let alone to the complex context of cities and certainly not to disadva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…Ye et al [17] showed that, by controlling groundwater withdrawal, land subsidence in Shanghai decreased to an average speed of 5.5 millimeter per year. Therefore, these detailed water-related policies must be accommodated in urban planning policies in order to increase the capacity of the adaptation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al [17] showed that, by controlling groundwater withdrawal, land subsidence in Shanghai decreased to an average speed of 5.5 millimeter per year. Therefore, these detailed water-related policies must be accommodated in urban planning policies in order to increase the capacity of the adaptation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of climate change are always locally measured and tackled and therefore have to be locally tailor-made [27], responding to the institutional arrangements of the local urban planning system. Hence, in order to be effective and balance flexibility and robustness, adaptation needs to match the institutional arrangements for planning and fit into the local planning processes [1]. Accordingly, in order to deal with the challenges of climate adaptation, the planning system needs a legal system that is firmly rooted in broadly accepted values as well as flexibility to adjust to local circumstances.…”
Section: Dilemma Of the Law: Flexibility Versus Robustnessmentioning
confidence: 99%
“…A strategy, firmly supported by a common understanding of the effects of climate change, starts with building common ground, which can function as a basis for the development of "goal entwinement" [1]. This can be understood as capacity building.…”
Section: Capacity Building In a Three-stage Proceduresmentioning
confidence: 99%
See 2 more Smart Citations